Breastfeeding Symptoms with Tongue- and Lip-Tie. Issue 1 (January 2023) - Hill, Rebecca R.; Richard, Melissa A.; Pados, Britt F.
Abstract: Purpose: The aims of this study were to describe maternal and infant symptoms relative to tongue- and lip-tie severity and describe changes in symptoms and feeding efficiency from pre- to post-frenotomy. Study Design and Methods: A one-group pre- and post-intervention study design was used. Data from a dental practice were collected from medical records of infants less than 1 year old who underwent a frenotomy procedure for tongue- and/or lip-tie. Infant and maternal symptoms were compared with severity of tongue- and lip-tie using binary logistic regression. Wilcoxon Signed Rank test compared pain scores and feeding duration pre- and post-frenotomy. Linear regression compared total number of symptoms reported pre-frenotomy with tongue- and lip-tie severity. Results: N = 121 dyads were included. More severe classifications of tongue- and lip-tie were significantly associated with certain infant and maternal symptoms pre-frenotomy. Improvements were noted in all reported infant symptoms post-frenotomy. Feeding duration times significantly decreased post-frenotomy. Clinical Implications: Infants and mothers experience problematic symptoms with feeding associated with tongue- and lip-tie. Nurses are the primary care providers during postpartum and should be alert to signs and symptoms that may suggest oral restrictions. Early evaluation and involvement of feeding experts may improve the breastfeeding experience of the dyad. Abstract : In this study, symptoms of tongue and lip-tie were studied before and after frenotomy in a group of 121 mother-baby dyads. More severe classifications of tongue and lip-tie were significantly associated with infant and maternal symptoms pre-frenotomy. Improvements were in noted in all reported infant symptoms post-frenotomy. Feeding duration times significantly decreased post-frenotomy. Infants and mothers experience problematic symptoms with feeding associated with tongue and lip-tie. Early evaluation and involvement of feeding experts may improve the breastfeeding experience of the dyad.